High energy-resolution electron energy loss spectroscopy and near infrared absorption study of cesium tungsten bronze and lanthanum hexaboride - Shuzheng Guo; Jingyi Huang; Na Ta; Fengze Cao; Sihua Ha; Shuai He; Jianli He; Luomeng Chao (Materials Letters: X)
Cs0.33WO3 nanoparticles exhibit strong localized surface plasmon resonance (LSPR), making them effective at absorbing near-infrared (NIR) light. However, effectively tuning the optical absorption of Cs0.33WO3 in the critical NIR range of 800–1000 nm has remained a major challenge. In this study, we employ aberration-corrected electron microscopy to conduct high-resolution electron energy loss spectroscopy (EELS) on both Cs0.33WO3 and LaB6 nanoparticles, reveal that the surface plasmon resonance in LaB6 nanoparticles occurs at a higher energy than in Cs0.33WO3, allowing LaB6 to absorb NIR light at shorter wavelengths. Based on this, we successfully adjusted the absorption characteristics of Cs0.33WO3 in the range of 800–1000 nm by utilizing the synergistic LSPR tuning of LaB6 nanoparticles.